The Need for Written Examinations and Interviews in the Appointment of Syarie Lawyers: An Analysis and Recommendations - Abdul Karim Ibrhim; Amirah Aqilah Mohd Zin; Mohd Sabree Nasri (Faculty of Syariah and Law, USIM, 2026)
This study examines the necessity of implementing written examinations and interviews in the appointment process of Syarie lawyers in Malaysia. The Syarie legal profession plays a vital role in safeguarding the rights of litigants in the Syariah Courts and ensuring that justice is upheld in accordance with Islamic law. However, inconsistencies in the qualification requirements—particularly written tests and interviews across different states have resulted in varying assessment standards and hindered the mobility of Syarie lawyers to practise in multiple jurisdictions. The key question that arises is whether a standardized system is needed to strengthen the integrity of the Syarie legal profession and enhance public confidence in the Islamic judicial institution. Accordingly, the objectives of this study are to identify the concept of Syarie lawyer appointments based on statutory provisions and Islamic principles, to assess the current implementation of written examinations and interviews, and to propose improvements to address existing inconsistencies. This research adopts a qualitative doctrinal approach through a comprehensive literature analysis of enactments, appointment procedures, books, academic articles, and journals. Additionally, semi-structured interviews were conducted to obtain empirical insights from officers and practitioners within the Syariah legal field. The findings reveal substantial differences among states in determining examination and interview requirements, resulting in inconsistent assessment standards and confusion among prospective candidates. The study proposes a standardised guideline covering aspects such as scoring methods, examination content, categories of candidates required to sit for written tests, and the publication of past examination questions as official references. Overall, this study contributes towards strengthening a more transparent and harmonised appointment system for Syarie lawyers nationwide, without undermining the jurisdictional authority of individual states. In conclusion, standardisation is deemed an essential step to ensure that the Syarie legal profession remains credible, respected, and continues to serve as a pillar of justice within Malaysia’s Islamic legal system.